Active power optimisation scheduling method for large-scale urban distribution networks with distributed photovoltaics considering the regulating capacity of the main network - Gong, Cheng; Wang, Wei; Zhang, Wenhan; Dong, Nan; Liu, Xuquan; Dong, Yechun; Zhang, Dongying (Frontiers in Energy Research, 2024)
Introduction When a distributed photovoltaic (PV) system has access to a large urban distribution network, the active balance is primarily borne by the main network gas unit; when the scale of the distributed PV system is very large, the main network can only provide limited regulation capacity, and the distribution network must determine the active optimal scheduling strategy. Methods This work proposes an active optimization scheduling model for the distribution network by considering the regulation capacity of the main network. In terms of the optimisation objectives, the maximum consumption of the distributed PVs and minimum power fluctuation at the demarcation point of the main distribution network are proposed as the main objectives, while the minimum total exchanged power in a cycle at the main distribution demarcation point and minimum distribution network loss are considered as the secondary objectives. In terms of constraints, it is proposed that the main network’s regulation capacity be characterized by the main network’s gas-fired unit creep constraints. A fast solution method for active optimization of the distribution network is designed herein to formulate the priority control order of the adjustable units according to the dispatch economic performances of various types of adjustable resources in the distribution network; this reduces the number of variables involved in the optimization at each step and improves the optimized solution speed. Results Finally, Simulation verification by IEEE 33-node distribution network arithmetic example based on Matlab simulation platform. Discussion Simulation results show the effectiveness of the method in achieving maximum PV consumption and reflecting the limited regulation capacity of the main grid.